The Global Development of Halal Food Industry: A Survey - Rininta Nurrachmi (Tazkia Islamic Finance and Business Review, 2017)
Abstract. This study aims to observe the existence of Halal food industry in developed and developing countries, and ways to increase the acceptance towards Halal products from non-Moslem societies. The approach is based on observation of the business environment of Halal food industry, online research and analysis of papers in journals. The finding indicates that although developed countries have less Moslem but the market share for Halal food is high. Countries with less Moslem population namely Thailand, United Kingdom and Australia can capture the opportunity of Halal food in the global market. Thus, most of Halal food exporters are coming from there. Halal food industry can be a catalyst to develop other potential sectors who get the negative impact from economic crisis in a country with less Moslem population. Countries namely Thailand, Australia, United Kingdom and Japan have applied commercial farm in their supply management to support their Halal food production. Furthermore, the awareness of consuming Halal food also come from non-Moslem due to the safer and freshness of the food. Hence it is important for producer to promote Halal food as being safety-compliant.